E-commerce strategy based on marketing techniques for Barcelona SC of Ecuador - López Flores, Renato Renee (2024)
Barcelona SC has its official store in the city of Guayaquil-Ecuador, but due to high investment costs it cannot open more physical stores in other cities and so far it has not ventured into electronic commerce; which causes dissatisfied customers. Therefore, the objective of this study was to develop an electronic commerce strategy for Barcelona SC, taking as reference the global impact soccer teams of Real Madrid CF and CA Boca Juniors. We worked with qualitative descriptive methodology with documentary design. The results allowed us to characterize the elements of electronic commerce of the aforementioned clubs and, based on them, establish a strategy for Barcelona SC. It was concluded that it is important for Barcelona SC to venture into electronic commerce to increase its sales, serve all fans and serve as an example for other sports clubs.